Strategi Dakwah Habib Jindan Dan Kyai Faiz Syukron: Retorika Dan Materi Dakwah Di Media Sosial - Harahap, Maratua Hasonangan; Zen, Muhamad; Fatmawati, Fatmawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This abstract discusses the da'wah strategies used by two prominenD da'wah figures, namely Habib Jindan and Kyai Faiz Syukron, in the context of social media. This research explores aspects of the rhetoric and preaching material they convey via online platforms. The rhetorical approach used by both of them will be analyzed, including the choice of words, delivery style, and persuasion strategies they employ. Apart from that, the preaching material they convey will also be evaluated to understand the main themes they raise, their approach to contemporary issues, and the way they convey religious messages in a modern context. By using content analysis methods and a qualitative approach, this research aims to provide a deeper understanding of how these two preaching figures use social media as a tool to spread religious teachings, influence public opinion, and build a large community of followers. It is hoped that the results of this research will provide new insight into da'wah strategies in the digital era and how online da'wah can be a significant force in shaping people's views on religion and spiritual values.